Evaluation of Security Vulnerabilities in the Single Submission Pengangkut System Using OWASP Top 10 - Adi Gilang Wahyu Aji; Ika Kurniawati (Journal of INISTA, 2026)
International trade in the era of globalization has rapidly grown thanks to information and communication technology (ICT), but this also presents new challenges related to data security and user information protection. In Indonesia, the National Single Window (LNSW) utilizes the Single Submission Pengangkut web application to support international trade. Although this application plays an important role, potential security vulnerabilities could lead to data breaches and financial losses. This study aims to test the security vulnerabilities of the application using Penetration Testing methods based on the OWASP Top 10 standard. Testing was conducted using tools such as Nmap, Nessus, Kali Linux, and Burp Suite to identify and exploit vulnerabilities. The results of the testing revealed three vulnerabilities that did not pass the security test: Insecure Design, Vulnerable and Outdated Components, and Identification and Authentication Failures. Based on assessments using the Common Vulnerability Scoring System (CVSS), it was found that Insecure Design has a Medium vulnerability rating, while Vulnerable and Outdated Components and Identification and Authentication Failures fall under the info category, meaning they do not directly impact the application's security. To address these vulnerabilities, it is recommended to implement restrictions in the document input process, perform regular software updates, and implement multi-factor authentication (MFA). This study shows that applying the OWASP Top 10 as a guideline in penetration testing is effective for identifying and evaluating security vulnerabilities in the Single Submission Pengangkut web application.